TINDAK TUTUR ILOKUSI DAN KESANTUNAN BERBAHASA PADA NOVEL ANDREA HIRATA - Ayu Purboningrum, Indah; Sumarwati, Sumarwati; Rohmadi, Muhammad (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Illocutionary speech acts are speech acts that are most often encountered in life to help the communication process between speakers and speech partners. Communication that is established usually needs to pay attention to the principles of language politeness. Both studies are not only found in life but can also be contained in novel literary works. This study aims to identify the form and function of illocutionary speech acts and language politeness in the interaction between teachers and students in Andrea Hirata's novel. This research is a descriptive qualitative research. The data sources in this research are the novels Sang Pemimpi and Guru Aini by Andrea Hirata. The sampling technique is done by purposive sampling technique. This research concludes that there are five forms of illocutionary speech acts in Andrea Hirata's novel, namely assertive illocutionary speech acts, directive illocutionary speech acts, declarative illocutionary speech acts, expressive illocutionary speech acts, and commissive illocutionary speech acts. There are also six maxims based on Geoffrey Leech's theory, namely the maxim of wisdom, the maxim of generosity, the maxim of respect, the maxim of simplicity, the maxim of agreement, and the maxim of sympathy in Andrea Hirata's novel. This research provides a treasure of knowledge about illocutionary speech acts and language politeness in the study of pragmatics.